A wearable device with inertial motion tracking and vibro-tactile feedback for aesthetic sport athletes Diving Coach Monitor - Kidman, E. M.; D'Souza, M. J. A.; Singh, S. P. N. (IEEE International Conference on Signal Processing, 2016)
Research into the kinematic training of elite divers shows a demand for diver training using biomechanical feedback. With suitable inertial data and tactile feedback, divers and their coaches could better understand their dives and failure modes. This would help improve technique and reduce fatigue during both training and competition, resulting in higher quality dives. We developed the Diving Coach Monitor (DCM) that can wire-lessly stream inertial data to an assistant as well as vibrotactially signal an athlete during a dive. The DCM is comprised of a wearable sensor module, worn by a diver and a smartphone application for the diver's coach. The diver's coach uses the smartphone application to signal the wearable sensor module, throughout the training session. The wearable sensor module receives the control commands and acts accordingly with one of the following actions: vibrate (to signal the diver); commence inertial data sampling; stop inertial data sampling and transmit data back to the smartphone application. While the DCM is water-proof, we trialled the DCM in a "dry-land" environment, as divers often train with trampoline spotting rigs and (occasionally) a safety harness. We also conducted multiple trial sessions with circus and gymnastic aerial apparatus and athletes. Our tests showed accurate measurement and low latency compared to video motion analysis.